Role plays in mathematical-logical development in initial education - Barahona, Clariza; Pinos, Geofre; Vistín , Manuel (Revista Universidad de Guayaquil, 2017)
The objective of this research is to adapt the research-action methodology to the learning of mathematics through the use of role play, that is, everyday situations in the child's life to transform them into a simulation in class with their classmates. Children tend to learn much better if they play while learning, it is easier to assimilate mathematics if they take roles within a "dramatization" that uses mathematics as the main object of their assigned role. This work focuses on making it easier to learn mathematics, demonstrating that mathematics can also be learned in another context, such as role play and not just in a notebook that shapes logical mathematical operations typical of their age. In addition, the present research leaves an applicable and fun precedent for future research to apply this methodology as a creative basis for new teaching-learning models in other areas of study.
Keywords: logical - mathematical development; role - play; research - action method; simulation